Model decomposition of robustness diagram with loop and time controls to Petri Net with considerations on resets - Castillo, John Albert R.; Malinao, Jasmine A. (2024)
The robustness diagram with loop and time controls is a multidimensional workflow model that can capture all three workflow dimensions, i.e. process, resource, and case. Thus, it can be used in system representations for real-world systems in the business and academic domains. In contrast to other workflow models, such as Class Diagram and Petri Net, tools that support the automated implementation and verification of Robustness Diagram with Loop and Time Controls are still not yet well-established. As such, previous literature introduced strategies for mapping the Robustness Diagram with Loop and Time Controls to other workflow models such as Class Diagram, Sequence Diagram, and Petri Net. A recent study focused on mapping the Robustness Diagram with Loop and Time Controls to Petri Net, emphasizing the reachability, soundness, and reuse of substructures. This mapping, however, is incomplete since some structures and behaviors in the Robustness Diagram with Loop and Time Controls were not captured. In this study, a novel mapping of the Robustness Diagram with Loop and Time Controls to Petri Net that addresses existing gaps was proposed. Such limitations addressed in this study include mapping the reset behavior of the reset-bound subsystem. This study revised the current mapping of MIX-JOIN. This study also proposed an additional mapping of the Robustness Diagram with Loop and Time Controls SPLIT structures such that these structures do not result in unsound Petri Nets. Additionally, this study was able to provide a method for mapping multiple abstract arcs present in the Robustness Diagram with Loop and Time Controls. Moreover, an overview, validation, and analysis of the proposed mapping algorithm in this study were provided. Finally, the output Petri Nets from the previous and proposed mappings were checked and compared in terms of structural and behavioral properties.
Undergraduate thesis (B.S. Computer Science) -- University of the Philippines, Tacloban.